Memórias e narrativas LGBTQIAP+ : uma análise discursiva sobre os processos de silenciamento no período escolar - Silva, João Vitor da (2025)
This dissertation investigates how public schools in the state of Mato Grosso contribute to the construction of subjectivities, specifically those of LGBTQIAP+ men, by examining the power dynamics and ideological forces that shape them. The research analyzes how narratives surrounding gender and sexuality are constructed and perpetuated within pedagogical practices, while also identifying how normative actions influence these processes, which will be questioned in order to promote social emancipation (BARROS, 2015). The specific objectives of the study are: (i) to highlight the relationships and differences in the subjective constitution processes of LGBTQIAP+ men throughout their educational trajectories; (ii) to analyze the statements of these individuals to reveal the mechanisms of silencing in public schools in Mato Grosso; and (iii) to understand the historical processes of exclusion and resistance of the LGBTQIAP+ population in the Mato Grosso region. The study adopts a qualitative approach guided by Critical Discourse Analysis (CDA), as proposed by Fairclough (2003), which allows for an examination of how language structures socially written power relations. More specifically within CDA, the category of interdiscursivity is used to map social discourses related to gender and sexuality in educational practices. The theoretical framework integrates: Critical Discourse Analysis (CHOULIARAKI; FAIRCLOUGH, 1999; FAIRCLOUGH, 2003), conjuncture studies (QUINALHA, 2014), and studies of gender and sexuality (PRECIADO, 2020; FOUCAULT, 2022; LOURO, 2022; LEMEBEL, 2023), with a focus on Queer Theory and Performativity (BUTLER, 2019; SALIH, 2012). Participants in the study are LGBTQIAP+ men who completed their basic education in schools in the state of Mato Grosso. The interest in this study is rooted in the desire to foster an interdisciplinary dialogue with social sciences to gain a deeper understanding of the epistemological implications raised by this research. The results revealed the school as a dynamic space for identity negotiations, influenced by normative discourses privileging heterosexuality. While political advances have secured rights for LGBTQIAP+ individuals, these rights remain fragile and subject to attack. Ultimately, the study emphasizes the need for schools to safeguard these rights and serve as inclusive spaces.